2023
DOI: 10.1093/glycob/cwad015
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of nondigestible Raffinose family oligosaccharides as prebiotics

Abstract: Based on factual scientific health claims, prebiotics has gained significant importance in ever-growing food and pharmaceutical industries. The diverse nature of distinct prebiotics influences the host differently in distinguishable patterns. Functional oligosaccharides are either plant-derived or commercially prepared. Raffinose, stachyose, and verbascose are three types of raffinose family oligosaccharides (RFOs) that have been extensively used as medicine, cosmetic, and food additives. These dietary fiber f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…The presence of stachyose and raffinose in Tofu can take on a health aspect in humans. In fact, these galacto-oligosaccharides (GOS), as prebiotics, improve the balance of the gastrointestinal microbiota, promoting the growth of beneficial bacteria and inhibiting the growth of pathogens [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of stachyose and raffinose in Tofu can take on a health aspect in humans. In fact, these galacto-oligosaccharides (GOS), as prebiotics, improve the balance of the gastrointestinal microbiota, promoting the growth of beneficial bacteria and inhibiting the growth of pathogens [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, Bacteroides rely on enzymes encoded by genes in PULs for RFO degradation. However, other gut commensals like Bifidobacterium and Lactobacillus harbor operons that encode dedicated RFO regulation, transport, and metabolism functions ( 51 , 53 , 57 ). This may reflect that Bacteroides are better adapted to preferentially degrade longer polysaccharides whereas other commensals are more efficient degraders of smaller oligosaccharides like RFOs or HMOs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the importance of RFOs in human health as prebiotics because they can modulate the abundance of beneficial bacteria in the gut ( 51 , 52 , 54 ). Because of their ability to influence the microbiota, it is important to elucidate the mechanism by which gut bacteria can utilize RFOs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight that these oligosaccharides are antinutrients since they are not digestible by humans but by their microbiota and, therefore, can cause several problems such as flatulence due to the metabolism of intestinal methanogenic bacteria [50]. However, recent articles have shown that consumption of raffinose-like oligosaccharides can also be related to an improvement of the gut microbiota ecology, in particular with the increase in the Bifidobacteria and Lactobacilli, which are characteristic for a healthy microbiota [51,52].…”
Section: Loadings On Sc3mentioning
confidence: 99%